Pro SQL server 2012 reporting services - McDonald, Brian (Apress, 2012)
Pro SQL Server 2012 Reporting Services opens the door to delivering customizable, web-enabled reports across your business at reasonable cost. Reporting Services is Microsofts enterprise-level reporting platform. It is included with many editions of SQL Server, and is something youll want to take advantage of if youre running SQL Server as your database engine. Reporting Services provides a full set of tools with which to create and deploy reports. Create interactive reports for business users. Define reporting models from which business users can generate their own ad hoc reports. Pull data from relational databases, from XML, and from other sources. Present that data to users in tabular and graphical forms, and more. Reporting Services experts Brian McDonald, Rodney Landrum, and Shawn McGehee show how to do all this and much more in this third edition of their longstanding book on the topic. Provides best practices for using Reporting Services Covers the very latest in new features for SQL Server 2012 Your key to delivering business intelligence across the enterprise